Soil hydro-physical Environment as Influenced by Different Biochar Amendments - Das, Shaon Kumar; Ghosh, Goutam Kumar (International Journal of Bio-resource and Stress Management, 2017)
Biochar acts as a soil conditioner, improving soil physical properties, nutrient use efficiency and thereby increasing plant growth. An experiment was conducted at ICAR-National Organic Farming Research Institute during the year 2016−17 in order to study the effect of different levels of biochar obtained from different biomass on selected soil hydro-physical properties. In this study, a sandy loam soil was amended with four different types of biochar (maize, Lantana camara, pine needle and black gram) at four different rates (0, 5.0, 7.5 and 10.0 t ha-1). The biochar were characterized for their physico-chemical properties. After biochar application selected soil hydro-physical properties were analyzed for bulk density, porosity, aggregate stability, mean weight diameter, hydraulic conductivity and water holding capacity. Maize biochar was showing best result for improving all the selected the soil physical properties compared to other type. With increasing rate of application of biochar soil physical properties also changed significantly. The results showed that bulk density decreased from 1.53 to 1.13 g cm-3 while porosity increased from 58.38 to 65.67. Aggregate stability and mean weight diameter increased from 4.13 and 2.51 to 8.29 and 2.83, respectively. But biochar amendment decreased the soil hydraulic conductivity from 0.41 to 0.16. Besides water holding capacity also increased from 11.37 to 19.8 g cm-3. Finally soil moisture content increased significantly from 19.1 to 25.7 for all the biochar. These results strongly suggest positive improvement of soil hydro-physical properties following addition of biochar amendment in sandy loam soil.